2009
DOI: 10.1002/adma.200803243
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Cost Fabrication of Transparent Hard Replica Molds for Imprinting Lithography

Abstract: A new and cost‐effective replica fabrication method for transparent and hard molds used in imprinting lithography is presented. The process uses a polymer copy as a carrier. Replicated hard molds eliminate the need for direct contact between the master and the patterned polymer on the substrate, and thus reduce contamination of the master.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…On the other hand, sufficient elasticity is crucial for the conformal contact. With the aim of solving this issue, many research efforts have been made and the multilayer soft mold [17,18] and surface modification method [19] seem to be good choices. In this study, we used an embedded glass to increase the stiffness of the PDMS mold in view of simplifying the fabrication process; besides, this improvement has no influence on the physical features of the PDMS mold, which can still maintain the conformal contact and absorb the solvent.…”
Section: B Fabrication Of the Glass-embedded Pdms Moldmentioning
confidence: 99%
“…On the other hand, sufficient elasticity is crucial for the conformal contact. With the aim of solving this issue, many research efforts have been made and the multilayer soft mold [17,18] and surface modification method [19] seem to be good choices. In this study, we used an embedded glass to increase the stiffness of the PDMS mold in view of simplifying the fabrication process; besides, this improvement has no influence on the physical features of the PDMS mold, which can still maintain the conformal contact and absorb the solvent.…”
Section: B Fabrication Of the Glass-embedded Pdms Moldmentioning
confidence: 99%
“…They are also relatively inefficient methods in terms of processing time and energy [2,3,6,9]. Therefore, some researchers have studied the replication of nano-scale patterns via the soft lithographic concept, which is more efficient and requires a lower processing cost [2,3,6,9,12]. One of the main advantages of soft lithography techniques is that the nanostructures can easily be transferred into the functional substrate so that thereby a number of possible applications can be realized [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Recently Kim et al introduced the PDMS coating technology onto various hard and soft molds including these stiffer polymers. The PDMS-coated molds showed good surface properties, i.e., low surface energy and low adhesion properties, like normal PDMS molds [ 17 , 18 ]. It was previously reported that to create a strong and highly stable PDMS coating, the oxidized polymer surface must be treated with 3-aminopropyltriethoxysilane [APTES] before PDMS deposition.…”
Section: Introductionmentioning
confidence: 99%